2022
DOI: 10.1097/md.0000000000032022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of HIFU in combination with TACE in unresectable pediatric HB: A randomized, controlled, single-center clinical trial

Abstract: Background: Hepatoblastoma (HB) is the most common liver tumor in children, and the main treatment for HB is currently surgery. Studies have shown that transcatheter arterial chemoembolization (TACE) combined with high intensity focused ultrasound (HIFU) has significant efficacy, but there are relatively few studies on TACE combined with HIFU in China. Objective: To investigate the effect of using HIFU combined with TACE on patients’ liver function impairment and immune function in pediatric HB patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Tumor markers were reduced to normal (69). The results of another randomized controlled trial suggested that 110 patients with unresectable hepatoblastoma treated with High Intensity Focused Ultrasound (HIFU) combined with TACE regimen had higher survival rates of 100%, 84%, and 16% at 1, 3, and 5 years, respectively (70). The above results support that TACE and various treatment options in combination with TACE may have some efficacy in difficult-to-resect hepatoblastoma, leading to longer survival times.…”
Section: Assistive Technologymentioning
confidence: 89%
“…Tumor markers were reduced to normal (69). The results of another randomized controlled trial suggested that 110 patients with unresectable hepatoblastoma treated with High Intensity Focused Ultrasound (HIFU) combined with TACE regimen had higher survival rates of 100%, 84%, and 16% at 1, 3, and 5 years, respectively (70). The above results support that TACE and various treatment options in combination with TACE may have some efficacy in difficult-to-resect hepatoblastoma, leading to longer survival times.…”
Section: Assistive Technologymentioning
confidence: 89%
“…The nomogram prediction model, which incorporates SIRI and clinicopathologic factors, has shown good predictive ability, suggesting its potential usefulness as a valuable tool for clinicians in formulating appropriate personalized treatment strategies. Moreover, alternative techniques, such as transarterial chemoembolization (TACE), radiofrequency ablation (RFA), and high-intensity focused ultrasound (HIFU), have been utilized in pediatric oncology ( 67 69 ). These techniques hold promise for patients with high preoperative inflammatory indexes, as they may effectively control tumor growth and allow for postponement of surgical treatment, leading to potentially improved outcomes for these children.…”
Section: Discussionmentioning
confidence: 99%